Analisis Online Review, Celebrity Endorsement, Kesadaran Halal terhadap Pembelian Fashion Halal - Rahmah, Rahmah; Sari, Diana (Management Department, Faculty of Economics and Business, Universitas Jambi, 2024)
With around 229 million Muslims, Indonesia is the largest Muslim-majority country. However, Indonesia is not in the number one position in every sector in the halal industry. This is contradictory to the reality in Indonesia because based on this data, Indonesia has the largest number of Muslims in 2023. This journal examines the influence of consumption behaviour on halal fashion among generation Z Muslims in Bandung. This study aims to determine whether online customer reviews, celebrity endorsement, and halal awareness have a significant effect on the purchase intention of halal fashion in the Shopee application. This study uses a quantitative approach with the Structural Equation Model (SEM) using SmartPLS 4 software. The number of samples obtained was 202 people according to the specified criteria, who are Muslim, aged 10-28 years, domiciled in Bandung, and have bought halal fashion products at Shopee. The results of the study indicate that each of the variables of online customer review, celebrity endorsement, and halal awareness has a positive and significant effect on the intention to buy halal fashion at Shopee for generation Z Muslims in Bandung.